2024
DOI: 10.55927/jfbd.v3i1.8602
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Celebrity Endorsement, Green Brand Image and Green Product Quality on Decisions to use Sharia Banking Product

Dimas Handoyo Putro,
Nurwahidin Nurwahidin,
Eko Tama Putra Saratian

Abstract: This research aims to analyze the influence of Celebrity Endorsement, Green Brand Image, and Green Product Quality on Decisions to Use Sharia Banking Products. The population in this study who had used sharia banking products. Sampling used Non-Probability sampling with Purposive Sampling technique, with a sample size of 120 respondents. The data analysis method in this research uses the Partial Least Square (Smart-PLS) program version 3.0. The research results prove that (1) Celebrity Endorsement has a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In other words, a choice must be available for someone to decide if the person does not make a purchase, the person is in a position to make a decision. Based on the definition above, it can be concluded that purchasing decisions, in this case, investment decisions, are part of consumer behavior regarding how consumer institutions or governments can make decisions or make selections to determine the type of financial instrument or which companies to fund (Saratian et al, 2022;Putro et al, 2024).…”
Section: Investment Decisionmentioning
confidence: 99%
“…In other words, a choice must be available for someone to decide if the person does not make a purchase, the person is in a position to make a decision. Based on the definition above, it can be concluded that purchasing decisions, in this case, investment decisions, are part of consumer behavior regarding how consumer institutions or governments can make decisions or make selections to determine the type of financial instrument or which companies to fund (Saratian et al, 2022;Putro et al, 2024).…”
Section: Investment Decisionmentioning
confidence: 99%